A best proximity point theorem for generalized Mizoguchi- Takahashi contractions - Semwal, Pushpendra; Dimri, R. (Global Journal of Mathematical Analysis, 2014)
The purpose of this paper is to provide sufficient conditions for the existence of a unique best proximity point for generalized Mizoguchi- Takahashi contractions. Our paper provides an extension of a result due to Gordji and Ramezani [3].   Keywords: Fixed point, best proximity point, P-property, Mizoguchi- Takahashi contractions.